Internal control – Internal check - يحيى, عباس حميد; محمد علي, نصيف جاسم (Journal of Economics and Administrative Sciences, 2013)
AbstractAll the economic  units whether productive or service units , strive to achieve specific objectives , their presence and continuity depend on them and the quality of the performance and service present to the society . This units to be able to achieve their objectives , must own basic assets to perform the activities , and apply laws , systems , and instructions , in addition to legal , managerial , and financial authorities . So this units to endeavor maintain this assets , in addition to sound application of laws ,systems . and procedures to enhance their performance . For this purpose arise the role of internal control and internal check in maintenance of assets and sound application of        laws and procedures . The problem of the research is in spite of the efforts of the departments of financials affairs and control and internal audit in the foundation of technical education to boost the control and financial performance of the foundation and it's institutes and colleges , there are no comprehensive written procedures for internal control to facilitate the maintenance of the assets and increase the efficiency of the operations . The research aims at establishing procedures and unified clear checks for the internal control system